2015
DOI: 10.3847/0004-637x/816/1/38
|View full text |Cite
|
Sign up to set email alerts
|

Chandra Observations of Eight Sources Discovered by Integral

Abstract: We report on 0.3-10 keV observations with the Chandra X-ray Observatory of eight hard X-ray sources discovered within 8°of the Galactic plane by the International Gamma-ray Astrophysics Laboratory satellite. The short (∼5 ks) Chandra observations of the IGR source fields have yielded very likely identifications of X-ray counterparts for three of the IGR sources: IGRJ14091-6108, IGRJ18088-2741, and IGRJ18381-0924. The first two have very hard spectra in the Chandra band that can be described by a power law w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
4
22
0
Order By: Relevance
“…The X-ray spectrum is also consistent with a CV/IP, and we confirm the presence of the strong iron line originally reported by Tomsick et al (2016) using Chandra measurements. With XMM, we find that the line emission is consistent with being a combination of lines from three ionization states with widths of 0.07 ± 0.04 keV and equivalent widths in the 160-320 eV range.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The X-ray spectrum is also consistent with a CV/IP, and we confirm the presence of the strong iron line originally reported by Tomsick et al (2016) using Chandra measurements. With XMM, we find that the line emission is consistent with being a combination of lines from three ionization states with widths of 0.07 ± 0.04 keV and equivalent widths in the 160-320 eV range.…”
Section: Discussionsupporting
confidence: 90%
“…We obtained low-resolution spectroscopy of the IGR J14091-6108 counterpart identified in Tomsick et al (2016), which is CXOU J140846.0-610754 and VVV J140845.99-610754.1. We used the FORS2 instrument with the 300V and 300I grisms combined with the GC435 and OG590 filters, respectively.…”
Section: Optical Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in most cases, sources are not classified until higher angular resolution X-ray observations are obtained, providing an image to identify extended sources or to improve the source localization, allowing for multi-wavelength counterparts to be found. Large X-ray follow-up programs include the use of the Neil Gehrels Swift Observatory X-ray Telescope (Swift/XRT; Landi et al 2017, and references therein) and the Chandra X-ray Observatory (e.g., Tomsick et al 2006Tomsick et al , 2008Tomsick et al , 2016a. The X-ray localizations enable optical and near-IR spectroscopy (e.g., Chaty et al 2008;Masetti et al 2013;Coleiro et al 2013;Fortin et al 2018), at which point confident source classifications are nearly always obtained.…”
Section: Introductionmentioning
confidence: 99%
“…IGR J18088−2741 was first reported in Krivonos et al (2012), and Tomsick et al (2016b) later identified it as CXOU J180839.8−274131 with Chandra. The fit to its combined Chandra and INTEGRAL spectra with a cut-off power law yields a very hard Γ ≈ −1.5 and E fold ≈ 4.8 keV, whereas the column density is N H < 7 × 10 21 cm −2 .…”
Section: Igr J18088−2741mentioning
confidence: 99%